Report on a Continuing Professional Education Needs Assessment among Library Personnel in The Bahamas - Bain, Elsie (International Journal of Bahamian Studies, 2016)
The College of The Bahamas Libraries and Instructional Media Services department is the premier academic and research library in the country. Its mission is to meet the needs and expectations of its patrons by acquiring and maintaining extensive physical and digital repositories of resources to support teaching and research. During a library symposium held in 2016 the planning committee surveyed attendees to gather information about their educational background and needs and goals for continuing professional education. The article summarizes the findings and potential implications of the survey.